THE BEAMING SUN: THE EFFECTIVENESS OF IMPERIAL JAPANESE RADAR AGAINST UNITED STATES AIRCRAFT DURING THE BATTLE FOR SAIPAN - Schaefer, Daniel J (East Carolina University)
This thesis endeavors to examine WWII-era Japanese radar emplacements and decipher the technology used during the battle for Saipan in 1944 in order to understand United States (US) aircraft losses. These Japanese search and fire-control radar emplacements allowed the detection and destruction of dozens of US aircraft through anti-aircraft fire on an unprecedented level. The thesis provides the first narrative of the US's underestimation of the effectiveness of Japanese radar capabilities and how it relates to the location of submerged aircraft. This thesis primarily utilizes archival research, archaeological survey, geographic information system (GIS) analysis, and predictive modeling to locate Japanese radar emplacements and downed US aircraft. The archival research includes obtaining Japanese and US radar technology documentation, US Navy after-action reports, and US and Japanese maps and intelligence reports of Saipan's defensive fortifications. An archaeological survey was conducted in Saipan at "Radar Hill," Naftan Peninsula, Mañagaha Island, and other potential locations of Japanese radar emplacements. Archeological data from the 2019-2023 East Carolina University/Defense POW/MIA Accounting Agency (DPAA) mission was utilized as a part of this research. The locations of lost US aircraft located in Tanapag Harbor and around Saipan were mapped, and a GIS model was created and analyzed to identify specific aircraft and any correlation they may have to the Japanese radar and anti-aircraft emplacements. Ultimately, this research attempts to predict the potential for aircraft losses in relation to radar location and range, thus contributing to site locations and individual site formation. Japanese radar technology is a severely neglected technological innovation in the historical record of the Pacific War, and Saipan and its archaeological signature provides a case study to examine its effectiveness.
Keywords: anti-aircraft; aircraft; predictive modeling; GIS; Radar--Military applications--Japan--History; World War, 1939-1945--Radar; World War, 1939-1945--United States--Aerial operations; Saipan, Battle of, Northern Mariana Islands, 1944